Ubuntu as a valued capability for university students in South Africa - Mikateko Mathebula; Carmen Martinez-Vargas (Journal of Student Affairs in Africa, 2023)
Universities are often described as institutions that can promote the wellbeing of their local populations. This is because they are central for advancing human development aims which support the aspirations of students and the communities from which they come. Nevertheless, we know this potential can be constrained by historical processes of oppression and negation of indigenous ways of being and doing. Applying the Capabilities Approach and Human Development paradigm as a normative framework for the outcomes of university education in the South African context, we argue for a focus on the centrality of capabilities (real freedoms) in assessing how well universities are doing to support student wellbeing. We pay special attention to one capability which we see as architectonic for other freedoms, which is Ubuntu. While Ubuntu is generally understood as a moral philosophy, in this paper we articulate it as a valued capability in the space of higher education. We also argue that it is a capability that has transformative and decolonial potential that can enable universities to promote student wellbeing if the conditions to practice it are in place.